Average Glandular Dose in Digital Mammography and Breast Tomosynthesis - Olgar, T.; Kahn, T.; Gosch, D. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: To determine the average glandular dose (AGD) in digital full-field mammography (2 D imaging mode) and in breast tomosynthesis (3 D imaging mode). Materials and Methods: Using the method described by Boone, the AGD was calculated from the exposure parameters of 2247 conventional 2 D mammograms and 984 mammograms in 3 D imaging mode of 641 patients examined with the digital mammographic system Hologic Selenia Dimensions. The breast glandular tissue content was estimated by the Hologic R2 Quantra automated volumetric breast density measurement tool for each patient from right craniocaudal (RCC) and left craniocaudal (LCC) images in 2 D imaging mode. Results: The mean compressed breast thickness (CBT) was 52.7 mm for craniocaudal (CC) and 56.0 mm for mediolateral oblique (MLO) views. The mean percentage of breast glandular tissue content was 18.0 % and 17.4 % for RCC and LCC projections, respectively. The mean AGD values in 2 D imaging mode per exposure for the standard breast were 1.57 mGy and 1.66 mGy, while the mean AGD values after correction for real breast composition were 1.82 mGy and 1.94 mGy for CC and MLO views, respectively. The mean AGD values in 3 D imaging mode per exposure for the standard breast were 2.19 mGy and 2.29 mGy, while the mean AGD values after correction for the real breast composition were 2.53 mGy and 2.63 mGy for CC and MLO views, respectively. No significant relationship was found between the AGD and CBT in 2 D imaging mode and a good correlation coefficient of 0.98 in 3 D imaging mode. Conclusion: In this study the mean calculated AGD per exposure in 3 D imaging mode was on average 34 % higher than for 2 D imaging mode for patients examined with the same CBT.
Keywords: breast tomosynthesis; average glandular dose; compressed breast thickness; digital mammography